Fur and feathers = los pelajes y las plumas - Halfmann, Janet; Klein, Laurie Allen (Mount Pleasant, SC : Sylvan Dell Publishing, 2010)
A story of a young girl who dreams that howling winds whisk fur and feathers right off her animal friends. Trying to help, she sews each of them a new "coat." But what kind do they need? Who needs fur, and what color? Who needs feathers, and why? Who needs scales, and should they be moist or dry? Includes "For Creative Minds" educational section.
004-009.
P-4.
AD 750
Accelerated Reader
Issued also as English and Spanish eBooks.
Keywords: Animals -- Classification -- Juvenile fiction; Adaptation (Biology) -- Juvenile fiction